2020
DOI: 10.35940/ijeat.c6032.029320
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nitride as a Reinforcement for Aluminium Metal Matrix Composites to Enhance Microstructural, Mechanical and Tribological Behavior

Abstract: In recent years, aluminium and its hybrid composites receiving more attention due to its excellent property combinations like improved mechanical properties, better wear and high corrosion resistance, ease to process and probably reduced production cost etc.. Composite is made of two phases one is matrix and another one is reinforcement. The performance of composite highly depends on some key factors that decide overall performance and they are properties of constituent phases, reinforcement size, reinforcemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Since reinforcement is a crucial parameter to obtain a definite set of properties, it should be chosen wisely. Several studies have already been conducted using oxides [6], carbides [7], nitrides [8], borides [9,10], sulphides [11], ceramic powders by various production methods. Some researchers have used agricultural [12,13] and industrial wastes [14,15] as well.…”
Section: Introductionmentioning
confidence: 99%
“…Since reinforcement is a crucial parameter to obtain a definite set of properties, it should be chosen wisely. Several studies have already been conducted using oxides [6], carbides [7], nitrides [8], borides [9,10], sulphides [11], ceramic powders by various production methods. Some researchers have used agricultural [12,13] and industrial wastes [14,15] as well.…”
Section: Introductionmentioning
confidence: 99%
“…Si 3 N 4 is a metal nitride that provides excellent creep properties and tensile strength with a reduction in ductility when it is reinforced in appropriate proportion with Al 6061 endowed this combination for structural applications [3,4]. Previous studies have shown that Al 6061 reinforced with Si 3 N 4 enhances corrosion resistance, wear resistance and metallurgical stability at high temperatures making this composite suitable for high wear and thermal-resistant applications [5]. Stir casting is the liquid state fabrication technique found to be a reliable production method for Al-Si 3 N 4 MMC offers good mechanical and tribological properties [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Al 6061 reinforced with Si 3 N 4 enhances corrosion resistance, wear resistance and metallurgical stability at high temperatures making this composite suitable for high wear and thermal-resistant applications [5]. Stir casting is the liquid state fabrication technique found to be a reliable production method for Al-Si 3 N 4 MMC offers good mechanical and tribological properties [3][4][5][6][7]. Stir casting produces outstanding characteristics in Al-Si 3 N 4 with regulated process conditions, and its low material density of 3.3 g/cm 3 and heat conductivity of 170-230 W/mk make it excellent for applications where weight is an issue [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum metal matrix composites have numerous applications in the engineering, marine, automotive, and aerospace sectors. Oxides [2], borides [3], nitrides [4], and carbides [3] are the most frequently used reinforcements for application-specific MMC.…”
Section: Introductionmentioning
confidence: 99%